Specific functions of Drosophila amyloid precursor-like protein in the development of nervous system and nonneural tissues. - Li, Y.; Liu, T.; Peng, Y.; Yuan, C.; Guo, A. (Journal of Neurobiology, 2004)
Drosophila amyloid precursor-like protein (APPL) is expressed extensively in the nervous system soon after neuronal differentiation. By utilizing different transgenic flies, we studied the physiological function of two APPL protein forms, membrane-bound form (mAPPL) and secreted form (sAPPL), in neural development. We found that neither deletion nor overexpression of APPL protein altered the gross structure of mushroom bodies in the adult brain. No changes were detected in cell types and their relative ration in embryo-derived cultures from all APPL mutants. However, the neurite length was significantly increased in mutants overexpressing mAPPL. In addition, mutants lacking sAPPL had numerous neurite branches with abnormal lamellate membrane structures (LMSs) and blebs, while no apoptosis was detected in these neurons. The abnormal neurite morphology was most likely due to the disorganization of the cytoskeleton, as shown by double staining of actin filaments and microtubules. Electrophysiologically, A-type K+ current was significantly enhanced, and spontaneous excitatory postsynaptic potentials (sEPSPs) were greatly increased in APPL mutants lacking sAPPL. Moreover, panneural overexpression of different forms of APPL protein generated different defects of wings and cuticle in adult flies. Taken together, our results suggest that both mAPPL and sAPPL play essential roles in the development of the central nervous system and nonneural tissues.